Investigation of viral infection in idiopathic pulmonary fibrosis among Iranian patients in Tehran. (March 2017) - Moradi, Pouya; Keyvani, Hossein; Javad Mousavi, Seyed-Ali; Karbalaie Niya, Mohammad Hadi; Esghaei, Maryam; Bokharaei-Salim, Farah; Ataei-Pirkooh, Angila; Monavari, Seyed Hamidreza
Abstract: Aim of the study: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease, which can be lethal with chronic complications. Viral infections may be associated with IPF and other fibrotic lung diseases. In the present study, we investigate for the first time in Iran the related viral etiology of IPF in order to detect three respiratory viruses; human adenovirus, enterovirus and bocavirus. Materials and methods: In this cross-sectional study which was supported by Iran University of Medical Sciences, Tehran, Iran. The diagnostic criteria for IPF were based on internationally accepted clinical and imaging criteria in accordance with the 2011 IPF guidelines. 30 nasopharyngeal (NP) swabs or broncho-alveolar lavage (BAL) samples were obtained from the lung of IPF patients that were diagnosed by a sophisticated practitioner from April 2015 to February 2016. Real-time (RT) polymerase chain reaction (PCR) method was performed to detect the three viruses. Fluorescence dye of a labeled probe recorded the results in order to create positive and negative controls. SPSS version 20 software was used to calculate basic descriptive and frequency features. Results: Of 30 specimens, 13 (43.4%) were male and 17 (56.6%) were female with the total mean age ± standard deviation 68.2 ± 12.0. RT-PCR assay results illustrated there was no infection of human adenovirus, enterovirus, and bocavirus detected in these samples. Significant results between IPF incidence and variables were not significant ( p  > 0.05). Conclusion: The causes of IPF in Iranian patients need more research although, based on the results of this study, there was no association between human adenovirus, enterovirus, bocavirus, and IPF. Highlights: Viruses may be associated with etiology of Idiopathic pulmonary fibrosis (IPF). Three viruses including human adeno, entero and boca were investigated however was observed no association between IPF and them.